Produksi Program Siaran Dakwah Radio - Taufik R Talalu (LPPM IAIN Sultan Amai Gorontalo, 2020)
This research aims at finding out to what extent the da’wah program on the radio is produced. The program existence with poor quality production, broadcasters and guest speakers personality who ignore the broadcasting style could result in dissatisfaction of public curiousity about Islamic topics as well as inability to foster public interest in learning Islam. This research is conducted in Radio Selebes Gorontalo using a qualitative method with a case study model. Techniques of data collection are interview and documentation studio. Techniques of data analysis are data collection, data reduction, data display, and drawing conclusion. Findings reveal that Selebes broadcasts three da’wah programs, namely Islam Discovery, Khazanah Islam, and Opus (Obrolan Puasa). Islam Discovery and Khazanah Islam are in the form of infotainment, while Opus is a talk show. These three programs are aired after going through starategic management stages, comprising program plans, program production and purchases, program execution, and program supervision and evaluation.